Protocol for a phase II, open-label exploratory study investigating the efficacy of fesoterodine for treatment of adult patients with spinal cord injury suffering from neurogenic detrusor overactivity for amelioration of autonomic dysreflexia. Issue 11 (21st November 2018) - Walter, Matthias; Ramirez, Andrea L; Lee, Amanda HX; Rapoport, Daniel; Kavanagh, Alex; Krassioukov, Andrei V
Abstract : Introduction: Managing and preventing risk factors associated with cardiovascular and cerebrovascular impairment is well studied in able-bodied individuals. However, individuals with spinal cord injury (SCI) at or above the spinal segment T6 are prone to experience autonomic dysreflexia (AD) but also to suffer from neurogenic detrusor overactivity (NDO). Treatment of NDO would not only improve lower urinary tract function but could also reduce the severity and frequency of life-threatening episodes of AD. Fesoterodine, an antimuscarinic drug, has been successfully employed as a first-line treatment for detrusor overactivity in individuals without an underlying neurological disorder. Thus, our aim is to investigate the efficacy of fesoterodine to improve NDO and ameliorate AD in individuals with SCI. Methods and analysis: This phase II, open-label exploratory, non-blinded, non-randomised, single-centre study will investigate the efficacy of fesoterodine to improve NDO and ameliorate AD in individuals with chronic SCI at or above T6. During screening, we will interview potential candidates (with a previous history of NDO and AD) and assess their injury severity. At baseline, we will perform cardiovascular and cerebrovascular monitoring (blood pressure (BP), heart rate and cerebral blood flow velocity) during urodynamics (UDS) and 24-hour ambulatory BP monitoring (ABPM) during daily life to assess severity and frequency of AD episodes (ie, maximum increase in systolic BP). The primary outcome is a reduction of artificially induced (during UDS) and spontaneous (during daily life) episodes of AD as a display of treatment efficacy. To answer this, we will repeat UDS and 24-hour ABPM during the last cycle of the treatment phase (12 weeks overall, ie, three cycles of 4 weeks each). At the end of each treatment cycle, participants will be asked to answer standardised questionnaires (AD symptoms and quality of life) and present bladder and bowel diaries, which will provide additional subjective information. Ethics and dissemination: The University of British Columbia Research Ethics Boards (H15-02364), Vancouver Coastal Health Research Institute (V15-02364) and Health Canada (205857) approved this study. The findings of the study will be published in peer-reviewed journals and presented at national and international scientific meetings. This protocol adheres to the Standard Protocol Items: Recommendations for Interventional Trials and CONsolidated Standards Of Reporting Trials statements. Trial registration number: NCT02676154 ; Pre-results.